2019
DOI: 10.1021/acssuschemeng.9b02642
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient and RecyclableShewanella xiamenensis-Grafted Graphene Oxide/Poly(vinyl alcohol) Biofilm Catalysts for Increased Cr(VI) Reduction

Abstract: An integrated assembled recyclable catalytic material was fabricated by grafting Shewanella xiamenensis (S. xiamenensis) onto poly­(vinyl alcohol)/graphene oxide films (denoted as S. xiamenensis–GO/PVA biofilms) with different GO-to-PVA mass ratios (i.e., 4:1, 2:1, 1:1, 1:2, and 1:4 in 10 mg of GO-PVA mixtures). During a 48 h test, the S. xiamenensis–GO/PVA biofilms demonstrated increased Cr­(VI) removal efficiency of up to 100% for 50 mg/L Cr­(VI). Moreover, the assembled films displayed desirable biocompatib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…This is since the air-drying method of GO cannot completely remove the water between the GO sheets, and even the air-dried GO contains 8% water (Szabó et al 2005). This confirmed that the GO component in the GO-PVA membrane has undergone a microbial modification and reduction process after the degradation experiment (Mehdinia et al 2014;Cobos et al 2018;Wang et al 2018;Camedda et al 2019;Luo et al 2019). Corrected Proof…”
Section: Verification Of Go-pva Functions In the Degradation Processmentioning
confidence: 71%
“…This is since the air-drying method of GO cannot completely remove the water between the GO sheets, and even the air-dried GO contains 8% water (Szabó et al 2005). This confirmed that the GO component in the GO-PVA membrane has undergone a microbial modification and reduction process after the degradation experiment (Mehdinia et al 2014;Cobos et al 2018;Wang et al 2018;Camedda et al 2019;Luo et al 2019). Corrected Proof…”
Section: Verification Of Go-pva Functions In the Degradation Processmentioning
confidence: 71%
“…Notably, the activity recovery of the immobilized laccase composite retained greater than 80% of its initial activity after 10 reaction cycles (Rouhani et al, 2018). Likewise, Luo et al (2019) fabricated a unique complex by grafting Shewanella xiamenensis biofilms onto graphene oxide/poly (vinyl alcohol) films (denoted as S. xiamenensis-GO/PVA complex) to enable Cr(VI) reduction in wastewater. Due to the large specific surface area of GO and favorable biocompatibility of poly(vinyl alcohol), an abundance of S. xiamenensis cells developed an ordered architecture based on the layered-skeleton of the GO sheets that orchestrated/arranged cell distribution.…”
Section: Eabbiofilm Heterojunctions Of Electrically Conductive Materialsmentioning
confidence: 99%
“…The S. xiamenensis-GO/PVA complex was effectively used for Cr(VI) bioreduction under aerobic conditions, circumventing many of the limitations experienced under the anaerobic conditions required by most conventional BESs (Li et al, 2019b;Middleton et al, 2003). Moreover, the catalytic efficacy of biofilms for Cr (VI) bioreduction progressively increased in subsequent reaction cycles, with the reaction time of the tenth cycle reduced to 9 h compared to 48 h in the control group (Luo et al, 2019). The ability to recycle the reaction system containing the living heterojunction complexes demonstrates the efficacy for practical/economical, large-scale applications of BESs.…”
Section: Eabbiofilm Heterojunctions Of Electrically Conductive Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Microbial extracellular electron transfer (EET) is a process by which microorganisms oxidize extracellular electron donors (e.g., lowmolecular-weighted organic carbon) to release electrons for their respiration concomitant with transporting electrons directly to external electron acceptors (Flemming and Wingender, 2010). Previous investigations reported that microbial EET processes were facilitated through direct contact between microorganisms and electron acceptors via microbial nanowires or specific c-type outer-membrane cytochromes (e.g., OmcB/C, OmcE, OmcZ and OmcS in Geobacter sulfurreducens) (Hernandez and Newman, 2001;Li et al, 2020b;Reguera et al, 2005), interactions with exogenous or endogenous electron shuttles (e.g., quinone-containing compounds) (Chen et al, 2017a;Chen et al, 2017b;Li et al, 2019), and reactions with conductive materials (e.g., active carbon, biochar and reduced graphene oxide) (Chen et al, 2018b;Chen et al, 2016;Luo et al, 2019). In spite of these advances, the selectivity of microbial electrocatalysis technology associated with specific genetically encoded expression is still a bottleneck that must be overcome before realizing this technology for practical applications (Liu et al, 2018a).…”
Section: Introductionmentioning
confidence: 99%